Analysis of the Relationship Between Energy Consumption and Economic Growth in Indonesia: An Empirical Perspective and Environmental Impact - Yuli Utami; Moh. Zaini; Yanti Mayasari Ginting (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study examines the relationship between energy consumption and the concept of economic growth in Indonesia, and evaluates its impact on carbon emissions from 2019 to 2025. In examining the relationship between variables, a mixed-form log-linear Cobb-Douglas production function model is used to adopt a dynamic approach with an explanatory design. Annual data are taken from the Indonesian Central Bureau of Statistics, Energy, and Development Indicators. The analysis stages include the Augmented Dickey-Fuller stationarity test, the Granger causality test, Ordinary Least Squares analysis estimation, and to ensure model validity, diagnostic testing. The estimation results show that energy consumption has a positive and significant effect on real Gross Domestic Product. The elasticity coefficient of 1.523 indicates that a one percent increase in energy consumption is associated with a 1.52 percent increase in output. The Granger causality test shows a one-way relationship from energy consumption to economic growth, reflecting the function of energy as the main driver of national production activities. The increase in energy consumption during the economic recovery period is also accompanied by an increase in carbon dioxide emissions, indicating a high carbon intensity in our economic structure. Dependence on fossil-based energy sources continues to be a major factor causing increasing environmental pressure. These findings highlight the need for policies that support energy mix diversification, increased efficiency, and accelerated renewable energy development that can secure long-term growth rates and ensure environmental stability.